MENINGKATKAN MOTIVASI BELAJAR MAHASISWA MELALUI PEMBELAJARAN MODEL PROBLEM SOLVING MATERI STOIKIOMETRI - Mukhlis Mukhlis (UIN AR-RANIRY, 2017)
The efforts to increase the student learning motivation was become a part of all importance in our studies. The studies activity was not signifinificant if only depend on main book, modul or another subject as atribute of student sucsefully. Learning models will be significanly good if a lecture could be sourch to increase of motivation student learning and found what his needed. Motivation activity will be forces every body to know somethings needed for him self. The student movation caused staying in intrinsics dan extrinsics models. The arm of this research was to determine the aplication effect of problem solving learning model in stoichiometry to increase the students motivation. Is the type/of this research was action research with pretest-posttest group design. The researching sample was given treatment by problem solving learning model. The data collection were done by a pretest and postest of learning motivation by questionnaire test for every circle. The data processed by t-test for different test between pretest and posttes. This research study conducted in Education Chemical Studies Program, of FTK UIN Ar-Raniry. The results activities and learning students motivation shown that the totals average scores increased from 2,583 into 3,25 and totals average learning students motivation of N-gain score from 0,38 to 0,76 included of â€œgoodâ€ and â€œhighâ€ category. By problem solving, model can be increase the student learning movitation and passion when solving each problem in stoichiometry subject.